2017
DOI: 10.1007/s12070-017-1056-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Topical Medication in Prevention of Post-extubation Subglottic Stenosis

Abstract: Iatrogenic laryngotracheal injury is the most serious complication of endotracheal intubation since this method of establishing airway was first described by Eugene Bouchut in 1858. Even today, subglottic stenosis is the most dreaded complication of intubation. This animal study is focused on the host tissue response to intubation induced injury resulting in subglottic stenosis and methods to prevent this complication. To assess the role of topically applied Mitomycin-C and Triamcinolone Acetonide in wound hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The rabbits receiving topical steroids had less respiratory distress than those receiving mitomycin‐C or controls. Histopathologic analysis also demonstrated that triamcinolone acetonide application altered wound healing, whereas mitomycin‐C application did not 21 . Cincik et al reported decreased fibrosis after subglottic trauma in rabbits treated with mitomycin‐C or 5 fluorouracil/triamcinolone injection as compared with controls, with no difference between the effects of the 2 drugs 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbits receiving topical steroids had less respiratory distress than those receiving mitomycin‐C or controls. Histopathologic analysis also demonstrated that triamcinolone acetonide application altered wound healing, whereas mitomycin‐C application did not 21 . Cincik et al reported decreased fibrosis after subglottic trauma in rabbits treated with mitomycin‐C or 5 fluorouracil/triamcinolone injection as compared with controls, with no difference between the effects of the 2 drugs 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic analysis also demonstrated that triamcinolone acetonide application altered wound healing, whereas mitomycin-C application did not. 21 Cincik et al reported decreased fibrosis after subglottic trauma in rabbits treated with mitomycin-C or 5 fluorouracil/triamcinolone injection as compared with controls, with no difference between the effects of the 2 drugs. 22 We believe that there may be an effect by ciprofloxacin on the bacterial load at the sight of airway injury, which acts synergistically with the anti-inflammatory effect of the dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…8 A 2017 study by Kumar demonstrated a significant decrease in respiratory distress in rabbits treated with topical triamcinolone compared to controls. 9 Sekioka et al found that serial triamcinolone acetide injections in infants with ASGS led to improvements in the patency of the subglottis. 10 However, not all studies have found post-injury steroids to be efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized controlled animal study describes the role of MMC and triamcinolone acetonide in rabbits with subglottic injury . The rabbits were divided into control, MMC only, steroid only, and MMC with steroid groups.…”
Section: Discussionmentioning
confidence: 99%